Sebastian Brant (1457-1521): europäisches Wissen in der Hand eines Intellektuellen der Frühen Neuzeit - Andersen, Peter; Henkel, Nikolaus (Kulturtopographie des alemannischen Raums, 2023)
As a representative of the intellectual elites of his time, Sebastian Brant (1457–1521) was active in various cultural fields (Latin and German poetry, pious literature and theology, law, book illustration). The contributions in this conference volume, which marks the 500th anniversary of Brant’s death, documents his influence and reach, which have extended far beyond their time, in those fields
Der 500. Todestag Sebastian Brants im Jahr 2021 war Anlass für eine fächerübergreifende internationale Tagung ... vom 3.-5. Oktober 2021 in Straßburg
Veröffentlicht: 19. Juni 2023
Keywords: Brant, Sebastian -- 1458-1521 -- Congresses; Deutschland; Europa; Europe; Germany; Konferenzschrift; Brant, Sebastian